The Futurum Instans and the Translation of Two Hebrew Participles in Genesis 38.29 and 40.10 - Makujina, John ca. Ende 20. Jh./Anfang 21. Jh. (The Bible translator, 2015)
This article argues against a proposal by Theophile J. Meek that the futurum instans (the imminent future, “about to”) represents the correct verbal aspect for כמשיב in Gen 38.29 and כפרחת in Gen 40.10. The reasons for rejecting the futurum instans in these constructions include Meek’s rigid view of aspect as it applies to the participle and the existence of less ambiguous constructions to communicate the imminent future. This article concludes by recommending that כמשיב ידו be translated as “as soon as he drew back his hand” and כפרחת as “as soon as it put forth its leaves.”